Avaliação da atividade antimicrobiana e estudo químico de espécies do gênero Marcetia (Melastomataceae) - Leite, Tonny Cley Campos (2009)
The Melastomataceae is a family of flowering plant with over 4500 species distribuited in 180 genera. This family has a pantropical distribution and in Brazil is the sixth largest family in number of species presenting more than 1500 species. The genus Marcetia is composed of 28 species that are characterized by endemism. In this context, we emphasize that 27 of the 28 species are endemic to the cadeia do espinhaço in Brazil. Among other aspects, the endemism of the genus can contribute to the lack of biological or chemical studies in the literature. This work describe the evaluation of antimicrobial activity of Marcetia spp and the isolation of chemical constituents present in active extracts. Initially it was elaborated a survey of the chemical constituents of Melastomataceae, and it was observed the family is composed flavonoids, triterpenes, steroids and hydrolysable tannins. Huberia, Lavoisier, Microlicia, Trembleya are he most commoney studied genera in the family (chapter 1). The antimicrobial activity of leaf hexanic extracts of four species of Marcetia (M. canescens, M. latifolia, M. macrophylla e M. taxifolia) against seven Gram-negative and Gram-positive and three yeasts is also described. Five of these microorganisms are sensitive (four bacterial and one yeast) and five are resistant to antibiotics (three bacteria and two yeasts). The leaf extracts of Marcetia analyzed in this study had higher activity against the Gram-positive bacteria compared to Gram-negative and the extract of M. latifolia was what more inhibited the growth of three microbial species. Subsequently these extracts were analyzed by gas chromatography showing to contain hydrocarbons and triterpenes. However these classes of compounds are being confirmed by GC-MS (chapter 2). In addition, was also evaluated the antimicrobial activity of EtOAc and MeOH extracts of four species of Marcetia previously mentioned. These species were tested against seven bacteria (four Gram-negative and three Gram-positive) and three yeasts, of which five are sensitive organisms (four bacterial and one yeast) and are resistant to five antibiotics (three bacteria and two yeasts). It was observed that all the plant species inhibited the growth of at least one microbial species. Highlighting, the AcOEt extracts of M. latifolia and MeOH M. taxifolia by the number of microorganisms that they were able to inhibit and AcOEt M. canescens and MeOH M. taxifolia by producing the largest halo of inhibition. All Marcetia extracts were analyzed by HPLC-DAD front the presence of flavonoids which are common in this genus (chapter 3). Due to the pronounced antimicrobial activity of the AcOEt extract of Marcetia latifolia, this extract was submitted to successive fractionations using liquid chromatography in open column packed with silica and eluted with solvents in increasing order of polarity. After these procedures and analysis by TLC and recrystallization of the fractions was possible to obtain a mixture of hydrocarbons, a binary mixture of triterpenes (not identified) and the flavone calycopterina. The structural identification of these natural compounds was based on 1H and 13C NMR, UV and MS.